Utilization of Non-Filter Cigarette Butt Extract as a Natural Inhibitor of Carbon Steel Using Extraction and Microwave-Assisted Extraction Methods - Micha Mahardika; Dina Alva Prastiwi (Jurnal Inovasi Pendidikan dan Sains, 2025)
Corrosion is one of the destructive processes that primarily affects metals through chemical or electrochemical reactions with their environment. An inhibitor is one of the methods used in corrosion control. A corrosion inhibitor functions to reduce the corrosion rate of a material. In 2024, 28.6% of the Indonesian population were reported as active smokers, which causes an increase in cigarette butt waste. Kretek cigarettes, whose main ingredient is tobacco, can be utilized as corrosion inhibitors due to their tannin content. This study aims to determine the corrosion rate, evaluate efficiency, and compare two extraction methods: maceration and Microwave-Assisted Extraction (MAE). MAE is an extraction method that uses microwave irradiation to accelerate selective extraction through rapid and efficient solvent heating. The extract obtained through maceration produced corrosion rates of 4.3, 4.8, 6.9, and 11.31 MPY. By comparison, the extract obtained using the MAE method showed corrosion rates of 0.7, 0.4, 0.3, and 0.15 MPY. In this study, the optimal results were observed at an acid concentration of 150 ppm, where the maceration method produced the lowest corrosion rate of 4.3 MPY, while the MAE method yielded the lowest corrosion rate of 0.15 MPY